Dynamic Model of Chloralkali Membrane Process. (2017) - Budiarto, T.; Esche, E.; Repke, J.U.; Leksono, E.
Abstract: Chloralkali is one of the most important and energy intensive processes in the chemical industry. The process produces chlorine through electrochemical conversion. The process's energy consumption is a major production cost for the chloralkali industry. Since the demand for energy efficiency and environmentally friendly processes in industry increases, ion exchange membranes are used intensively in the process. One of the prospective energy sources for this process is renewable energy, which shows strong fluctuations and highly unpredictable behavior. Dynamic behavior of the process becomes important to measure and predict the feasibility of the process. Therefore, modelling of the process dynamics is required. Rigorous model of material balance and voltage balance of the process are developed and investigated in this paper. The material transport phenomena inside the electrolyser are modelled considering a number of driving forces. The developed model also predicts the voltage and current density of the cell. The process simulation result is compared to experimental data.